Social media influencers and sadaqah contribution among university students: Case of International Islamic University Malaysia - Ariffin, Muhammad Irwan; Nasaruddin, Muhammad Ghazi Zufar; Maulana, Ahsan Yusuf; Ameer, Abdulbarry Sultan (Review of Islamic Social Finance and Entrepreneurship, 2025)
Purpose – This study examines how social media influencers shape students’ willingness to engage in sadaqah (voluntary charity) at the International Islamic University Malaysia (IIUM), using the theory of planned behavior (TPB) as the guiding framework.Methodology – A mixed-methods design was employed, combining a survey of 150 students with semi-structured interviews with three influencers active in charitable campaigns. A descriptive analysis of TPB constructs (attitude, subjective norm, perceived behavioral control, and behavioral intention) was conducted alongside thematic analysis of the interview data.Findings – Students reported high exposure to influencer-promoted campaigns, particularly on Instagram and TikTok. Attitudes toward sadaqah were positive, and subjective norms were influential, as many felt encouraged to donate when their peers participated. However, financial constraints and trust-related concerns limit donations and underscore perceived behavioral control as a barrier. Influencers have highlighted the importance of emotional storytelling, transparency, and alignment with Islamic values in motivating contributions.Implications – Campaigns should pair credible, value-congruent influencers with platforms that have clear Shariah governance, transparent fund allocation, and visible verification to build trust; lower behavioral frictions through micro and recurring donation options, simple payment flows, and salient security cues; and leverage subjective norms by embedding peer-sharing prompts and social proof. Universities and NGOs can co-create cause-fit content with emotional storytelling and real-time impact updates to convert intentions into actual donations.Originality – This study is among the first to explore influencer-led sadaqah campaigns in Malaysia by integrating TPB with insights from Islamic social finance and digital philanthropy.